Trends and patterns in the recent accumulation and oxygen isotopes in coastal Dronning Maud Land, Antarctica: interpretations from shallow ice cores - Isaksson, Elisabeth; Melvold, Kjetil (Annals of Glaciology, 2002)
To investigate recent variability in accumulation and δ18O, we synthesize data from five snow cores, covering the period 1932–96, from the sector 16˚38’ W–4˚48’ E in coastal Dronning Maud Land (DML), Antarctica. the δ18O records from the different sites are remarkably similar and suggest a common stable moisture source for this coastal section of DML. While the accumulation pattern is local, and specific features restricted to the individual sites, the overall accumulation pattern is related to the temperature variability as indicated by coastal instrumental records. Accumulation and δ18O correlate between 1955 and 1985 but deviate thereafter, with the proxy-temperature record showing a positive trend while accumulation decreased. This occurs at the same time as an increase in sea-ice extent in the area, which may have resulted in circulation changes and more northerly storm paths. Both stacked accumulation and δ18O records show that large-scale atmospheric signals, as well as some pronounced individual events, are recorded in DML coastal ice cores.
Keywords: Dronning Maud Land; glasiologi; iskjerner

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi